Examining some fields within human resources management - Dienesné Kovács, Erzsébet; Gergely, Éva (Applied Studies in Agribusiness and Commerce, 2009)
Human resources management is one of the management functions, dealing with people as the essential resource of the organization. This function aims at the most efficient usage of employees in order to realize both organizational and individual goals. Nowadays high significance is attributed to human resources management, since the human factor is the resource that determines the success of an organization. The results of a company are in proportion with the knowledge and talent of the people on its payroll. Human talent and knowledge can be utilized to the greatest extent in case management is able to motivate employees to meet not only the necessary requirements but also to achieve the highest possible results. Human resources management consists of several fields of activities, among which the following are the most important: analysis, planning and assessment of the scope of activities, human resources planning, workforce supply, performance assessment, motivation, developing human resources, labour relations, labour safety, HEM information system. Our studies cover a few fields within human resources management. Our research has been carried out at organizations in Hajdú-Bihar County. The study is based on questionnaires, which have been processed by computers and evaluated using statistical methods.